The meltdown : Diary of wimpy kid - "Kinney, Jeff" (Puffin Books: London, 2018)
When snow shuts down Greg Heffley's middle school, his neighborhood transforms into a wintry battlefield. Rival groups fight over territory, build massive snow forts, and stage epic snowball fights. And in the crosshairs are Greg and his trusty best friend, Rowley Jefferson. It's a fight for survival as Greg and Rowley navigate alliances, betrayals, and warring gangs in a neighborhood meltdown. When the snow clears, will Greg and Rowley emerge as heroes? Or will they even survive to see another day?
Keywords: English Fiction-Diary fiction